1988
DOI: 10.1523/jneurosci.08-03-01063.1988
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation and maturation of embryonal carcinoma-derived neurons in cell culture

Abstract: We have previously shown that retinoic acid-treated cultures of the P19 line of embryonal carcinoma cells differentiate into neurons, glia, and fibroblast-like cells (Jones-Villeneuve et al., 1982). We report here that the monoclonal antibody HNK-1 reacts with the neurons at a very early stage of their differentiation and is, therefore, an early marker of the neuronal lineage. Cells in differentiated P 19 cultures synthesized acetylcholine but not catecholamines, suggesting that at least some of the neurons ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
135
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(141 citation statements)
references
References 38 publications
6
135
0
Order By: Relevance
“…To induce neural differentiation, SLCs were treated with RA, which has been introduced as a neural inducer in mouse and human embryonal carcinoma cells (Andrews et al 1984;McBurney et al 1988;Staines et al 1994) and mouse ESCs in vitro (Rohweddel et al 1999;Pacherník et al 2005). Present results indicated that RA could induce neural differentiation in SLCs 7 days after treatment, as confirmed by detection of GT3 and GD3 neural markers.…”
Section: Discussionmentioning
confidence: 99%
“…To induce neural differentiation, SLCs were treated with RA, which has been introduced as a neural inducer in mouse and human embryonal carcinoma cells (Andrews et al 1984;McBurney et al 1988;Staines et al 1994) and mouse ESCs in vitro (Rohweddel et al 1999;Pacherník et al 2005). Present results indicated that RA could induce neural differentiation in SLCs 7 days after treatment, as confirmed by detection of GT3 and GD3 neural markers.…”
Section: Discussionmentioning
confidence: 99%
“…Cytoplasmic and nuclear soluble fractions were prepared from CGNs as described previously (Taniguchi et al, 2000). Embryonal carcinoma P19 cells were induced to differentiate into neurons as described previously (McBurney et al, 1988). The equal amounts of proteins (25-30 g) were separated by 10% SDS-PAGE, blotted onto Immobilon membrane (Millipore, Billerica, MA), and incubated with antibodies against necdin (NC243, 1:1000), ␤-tubulin (1: 1000; MA Biomedicals, Irvine, CA), and phospho-specific Rb (Ser795, 1:300; New England Biolabs, Beverly, MA).…”
Section: Methodsmentioning
confidence: 99%
“…We ®rst tried to discover the physiological function of the neurone-speci®c Hu proteins using two neurogenic cell lines: rat pheochromocytoma cell line PC12, and mouse embryonal carcinoma cell line P19, which differentiate into neurone-like cells in response to nerve growth factor (NGF) and retinoic acid, respectively (Jones-Villeneuve et al 1982;Greene et al 1987;McBurney et al 1988). To examine the endogenous levels of Hu proteins in PC12 cells, we ®rst performed an immuno¯uorescence analysis using monoclonal antibody 16A11, which speci®cally recognizes the mammalian Hu proteins, except for HuR (Marusich et al 1994) (Fig.…”
Section: Induction Of Neurite Outgrowth By Over-expression Of Neuronementioning
confidence: 99%